The natural history of nodding syndrome. Issue 6 (27th December 2018) - Idro, Richard; Ogwang, Rodney; Kayongo, Edward; Gumisiriza, Norbert; Lanyero, Agnes; Kakooza‐Mwesige, Angelina; Opar, Bernard
ABSTRACT: Aims . Nodding syndrome is a poorly understood acquired disorder affecting children in sub‐Saharan Africa. The aetiology and pathogenesis are unknown, and no specific treatment is available. Affected children have a distinctive feature (repeated clusters of head nodding) and progressively develop many other features. In an earlier pilot study, we proposed a five‐level clinical staging system. The present study aimed to describe the early features and natural history of nodding syndrome and refine the proposed clinical stages. Methods . This was a retrospective study of the progressive development of symptoms and complications of nodding syndrome. Participants were a cohort of patients who had been identified by community health workers and were referred for treatment. A detailed history was obtained to document the chronological development of symptoms before and after onset of head nodding and a physical examination and disability assessment performed by a team of clinicians and therapists. Results . A total of 210 children were recruited. The mean age at the onset of head nodding was 7.5 (SD: 3.0) years. Five overlapping clinical stages were recognised: prodromal, head nodding, convulsive seizures, multiple impairments, and severe disability stages. Clinical features before the onset of head nodding (prodromal features) included periods of staring blankly or being inattentive, complaints of dizziness, excessive sleepiness, lethargy, and general body weakness, all occurring two weeks to 24 months before nodding developed. After the onset of head nodding, patients progressively developed convulsive seizures, cognitive and psychiatric dysfunction, physical deformities, growth arrest, and eventually, in some patients, severe disability. Conclusions . The description of the natural history of nodding syndrome and especially the prodromal features has the potential of providing a means for the early identification of at‐risk patients and the prompt initiation of interventions before extensive brain injury develops. The wide spectrum of symptoms and complications emphasises the need for multi‐disciplinary investigations and care.